Transjugular intrahepatic portosystemic shunt through isolated persistent left superior vena cava: Case report and review of the literature - Hongcheng Ren; Bin Wang; Changgang Shao; Guoqing Chi; Rui Liu; Yanhong Bai; Hongbo Zu; Mingchao Ding; Huaming Wang (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Transjugular intrahepatic portosystemic shunt (TIPS) was routinely used via the right internal jugular vein to establish a shunt pathway from the portal vein to the hepatic vein for treatment of complications of portal hypertension. Only a few case reports from the existing literature have demonstrated that successful puncture of the right branch of intrahepatic portal vein in TIPS by the left internal jugular vein, under the condition of the congenital central venous anomaly such as persistent left superior vena cava with absent right superior vena cava. This report describes TIPS conducted via the left branch of portal vein in a patient with generic bare stent/ stent-graft combination.